Haemonchus contortus parasitic stages development and host immune responses in lambs of different sheep breeds - Okino, Cintia Hiromi; Bello, Hornblenda Joaquina Silva; Niciura, Simone Cristina Méo; Melito, Gláucia Roberta; Cunha, Amanda Freitas da; Costa, Estevão Camillo da; de Campos, Emanuelle Martins; Kapritchkoff, Rafaela Tami Ikeda [UNESP]; Minho, Alessandro Pelegrine; Esteves, Sérgio Novita; Chagas, Ana Carolina de Souza (Elsevier, 2025)
Variable host resistance against Haemonchus contortus infection was extensively associated with sheep breed, but the mechanisms responsible for the enhanced resistance remains scarcely elucidated. The aim of the present study was compare the phenotypic profile of three breeds (Santa Inês, Texel and White Dorper) with the relative expression of immune-related genes in the abomasal mucosa of sheep breeds infected with H. contortus. Besides, these phenotypic profiles were compared with relative expression of immune related genes in the animal abomasum. Decreasing resistance against H. contortus infection among sheep breeds was observed in the following order: Santa Inês, Texel and White Dorper. Differential local immune responses were developed during chronic infection, wherein both Santa Inês and White Dorper presented high activity of innate receptors, especially TLR2, while Th2 related transcripts trended to be superior in the Texel lambs. The White Dorper lambs also presented increased local inflammation since most inflammatory related genes, including the pro-inflammatory mediators NFKBIA and IL1B, and anti-inflammatory cytokines IL10 and TGF were upregulated. The host responses to different parasite stages were characterised by TLR2 activity during earlier stages, while complement activity (CFI) was involved in the clearance of latter parasite stages. Further, TLR4 activity affected the responses to both early and late parasite stages. To our knowledge, this is the first study to point out for differential immune responses among sheep breeds and to different H. contortus parasitic stages. The better elucidation of these host-parasite interactions may improve the immune-prophylactic management of haemonchosis.